Effects of short-term cash and food incentives on food insecurity and nutrition among HIV-infected adults in Tanzania. (1st March 2019) - Fahey, Carolyn A.; Njau, Prosper F.; Dow, William H.; Kapologwe, Ntuli A.; McCoy, Sandra I.
Abstract : Objective: Food insecurity impedes antiretroviral therapy (ART) adherence. We previously demonstrated that short-term cash and food incentives increased ART possession and retention in HIV services in Tanzania. To elucidate potential pathways that led to these achievements, we examined whether incentives also improved food insecurity. Design: Three-arm randomized controlled trial. Methods: From 2013 to 2015, 805 food-insecure adult ART initiates (⩽90 days) at three clinics were randomized to receive cash or food transfers (∼$11 per month for ⩽6 months, conditional on visit attendance) or standard-of-care (SOC) services. We assessed changes from baseline to 6 and 12 months in: food insecurity (severe; access; dietary diversity), nutritional status (body weight; BMI), and work status. Difference-in-differences average treatment effects were estimated using inverse-probability-of-censoring-weighted longitudinal regression models. Results: The modified intention-to-treat analysis included 777 nonpregnant participants with 41.6% severe food insecurity. All three study groups experienced improvements from baseline in food insecurity, nutritional status, and work status. After 6 months, severe food insecurity declined within the cash (−31.4% points to 11.5%) and food (−30.3 to 10.4%) groups, but not within the SOC. Relative to the SOC, severe food insecurity decreased by an additional 24.3% points for cash (95% CI −45.0 to −3.5) and 23.3% percent points for food (95% CI −43.8 to −2.7). Neither intervention augmented improvements in severe food insecurity at 12 months, nor food access, dietary diversity, nutritional status, or work status at 6 or 12 months. Conclusion: Small cash and food transfers provided at treatment initiation may mitigate severe food insecurity. These effects may have facilitated previously observed improvements in ART adherence. Abstract : Supplemental Digital Content is available in the text